1993
DOI: 10.1002/1520-6297(199301)9:1<57::aid-agr2720090106>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of perceived product attributes on the perception of beef

Abstract: The objective of this study was to identify perceived characteristics of beef which impact quality perception. Results indicate that concerns with beef related to cholesterol and calorie content, artificial ingredients, convenience characteristics, how it is displayed in the store, and expense each significantly adversely affected quality perception. 0 1993 John Wiley & Sons, Inc.Changes in consumer lifestyles and the impacts of these changes on product selection are well recognized by processors and marketers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Increased concern for one's health (e.g., fat and cholesterol content) has certainly become one of the most important determinants of U.S. consumers' demand for beef products (Lusk & Schroeder, 2004;Menkhaus, Colin, Whipple, & Field, 1993;Ward, 2004;Ward, Lusk, & Dutton, 2008). Evidence showed that consumers are willing to pay a higher price for reduced fat content in 2 USDA (2013) defines "natural" as "a product containing no artificial ingredient or added color and is only minimally processed.…”
Section: Attribute Selectionmentioning
confidence: 99%
“…Increased concern for one's health (e.g., fat and cholesterol content) has certainly become one of the most important determinants of U.S. consumers' demand for beef products (Lusk & Schroeder, 2004;Menkhaus, Colin, Whipple, & Field, 1993;Ward, 2004;Ward, Lusk, & Dutton, 2008). Evidence showed that consumers are willing to pay a higher price for reduced fat content in 2 USDA (2013) defines "natural" as "a product containing no artificial ingredient or added color and is only minimally processed.…”
Section: Attribute Selectionmentioning
confidence: 99%
“…Initial research was based on industry reports (CBEF 1994; U.S. Meat Export Federation 1994) and meetings with Canadian beef industry representatives, government experts and Korean officials. On the basis of assessments from these sources and published market research findings such as Menkhaus et al (1993Menkhaus et al ( , 1990Menkhaus et al ( , 1988, several beef product factors and levels were identified to be of importance. The factors identified as major attributes in decisions to purchase beef include the country-of-origin of the beef, its price, the product quality or grade and the product specification.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The declining demand for beef, the growing demand for poultry, and the leveling off of demand for pork characterize the well-known consumption shift from red to white meat [1]. Driving the shift is consumers' increasing demand for healthy meat and meat products [2]. In fact, the attributes related to meat safety have become a critical component in motivating consumers to make food selection [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…A study from the USDA ranked health concerns as the number one factor influencing consumer demand for meat products [1], and choice experiment studies confirmed consumers' willingness to pay (WTP) for products with a USDA certified organic label [5]. Discussion in a broader spectrum regarding meat markets and consumer preferences could be referenced to many other studies [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%